2022
DOI: 10.3390/ijms23031341
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Epigenetics in Obesity: The Role of Lifestyle and Therapeutic Interventions

Abstract: Obesity has become a global epidemic that has a negative impact on population health and the economy of nations. Genetic predispositions have been demonstrated to have a substantial role in the unbalanced energy metabolism seen in obesity. However, these genetic variations cannot entirely explain the massive growth in obesity over the last few decades. Accumulating evidence suggests that modern lifestyle characteristics such as the intake of energy-dense foods, adopting sedentary behavior, or exposure to envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 159 publications
1
76
0
Order By: Relevance
“…DNA methylation is the most studied [ 46 ] and consists of the covalent binding of a methyl group to a cytosine residue in the DNA, at sites where cytosines are followed by guanines (CpG sites). This process is mediated by methyltransferases and its dysregulation (either hypermethylation or hypomethylation) can alter gene transcription and lead to several diseases [ 47 ].…”
Section: Genetics Epigenetics and Mitochondrial Factors Related To Ob...mentioning
confidence: 99%
“…DNA methylation is the most studied [ 46 ] and consists of the covalent binding of a methyl group to a cytosine residue in the DNA, at sites where cytosines are followed by guanines (CpG sites). This process is mediated by methyltransferases and its dysregulation (either hypermethylation or hypomethylation) can alter gene transcription and lead to several diseases [ 47 ].…”
Section: Genetics Epigenetics and Mitochondrial Factors Related To Ob...mentioning
confidence: 99%
“…In this regard, Jiménez-Navarro et al revealed a significant and nonsignificant elevation in mRNA levels of IRS1 and AKT2, respectively, in circulating leukocytes of patients diagnosed with type 2 diabetes along with coronary defect [67]. In parallel, it was shown that PIK3R1 (p85α) expression was increased in type 2 diabetes and was associated with insulin resistance through PI 3-kinase mechanisms [68,69]. Moreover, Zhao et al illustrated the role of PIK3R1 as hub genes with 11 connections to other genes in CHD development [70].…”
Section: Discussionmentioning
confidence: 98%
“…A high-fat diet (HFD), for example, is linked to altering the epigenome and raising the risk of obesity. A clinical trial utilizing an HFD for five days found an increase in the methylation of PPARG [ 44 ]. Other notable epigenomic changes occur with an increased expression of histone deacetylases (HDAC): HDAC5, HDAC8, and HDAC9.…”
Section: Factors Affecting the Development Of Obesitymentioning
confidence: 99%
“…Other notable epigenomic changes occur with an increased expression of histone deacetylases (HDAC): HDAC5, HDAC8, and HDAC9. These enzymes alter the expression of the genes responsible for metabolism and appetite regulation, leading to an increased propensity for obesity [ 44 ].…”
Section: Factors Affecting the Development Of Obesitymentioning
confidence: 99%